2018
DOI: 10.1172/jci.insight.99048
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-targeted CD4+ CAR T cells mediate superior antitumor activity

Abstract: Chimeric antigen receptor-modified (CAR-modified) T cells have shown promising therapeutic effects for hematological malignancies, yet limited and inconsistent efficacy against solid tumors. The refinement of CAR therapy requires an understanding of the optimal characteristics of the cellular products, including the appropriate composition of CD4+ and CD8+ subsets. Here, we investigated the differential antitumor effect of CD4+ and CD8+ CAR T cells targeting glioblastoma-associated (GBM-associated) antigen IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 71 publications
11
157
0
Order By: Relevance
“…Thus, NeoAg‐reactive TCRm antibodies could be used with current CAR technology to provide specificity against NeoAgs in the near future. Surprisingly, recent mouse studies have highlighted that CD4 + CAR T cells alone mediate superior antitumor activity relative to their CD8 + counterparts 90–93 . Whereas the cytotoxic capacity of CD4 + T cells in tumor models is hardly novel, 80,94–96 in the context of CAR T therapy, CD4 + T cells also mediate tumor cytotoxicity directly, resist AICD, do not help CTLs resist exhaustion, and are in fact impeded by their CD8 + compatriots 90 .…”
Section: Help In Therapeutic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NeoAg‐reactive TCRm antibodies could be used with current CAR technology to provide specificity against NeoAgs in the near future. Surprisingly, recent mouse studies have highlighted that CD4 + CAR T cells alone mediate superior antitumor activity relative to their CD8 + counterparts 90–93 . Whereas the cytotoxic capacity of CD4 + T cells in tumor models is hardly novel, 80,94–96 in the context of CAR T therapy, CD4 + T cells also mediate tumor cytotoxicity directly, resist AICD, do not help CTLs resist exhaustion, and are in fact impeded by their CD8 + compatriots 90 .…”
Section: Help In Therapeutic Contextmentioning
confidence: 99%
“…Surprisingly, recent mouse studies have highlighted that CD4 + CAR T cells alone mediate superior antitumor activity relative to their CD8 + counterparts. [90][91][92][93] Whereas the cytotoxic capacity of CD4 + T cells in tumor models is hardly novel, 80,[94][95][96] in the context of CAR T therapy, CD4 + T cells also mediate tumor cytotoxicity directly, resist AICD, do not help CTLs resist exhaustion, and are in fact impeded by their CD8 + compatriots. 90 Future CAR trials should test whether enriched CD4 + T cells are similarly superior in humans as they are in mice.…”
Section: Adoptive Cellular Therapymentioning
confidence: 99%
“…109 Improvements in activity and persistence of IL13Ra2-CAR-T cells have also been observed when the T cells were engineered to express transgenic IL-15 although antigen escape was more common. Surprisingly, delivery of a purified CD4 + population of IL-13Ra2-CAR-T cells resulted in enhanced antitumor activity and persistence compared to either purified CD8 + or mixed CD4 + /CD8 + populations.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Surprisingly, delivery of a purified CD4 + population of IL-13Ra2-CAR-T cells resulted in enhanced antitumor activity and persistence compared to either purified CD8 + or mixed CD4 + /CD8 + populations. 109 Improvements in activity and persistence of IL13Ra2-CAR-T cells have also been observed when the T cells were engineered to express transgenic IL-15 although antigen escape was more common. 110 And finally, NKG2D-based CAR-T cells displayed synergistically enhanced antitumor activity when the mice were also treated with radiation, an effect attributed not only to radiation-induced upregulation of NKG2D ligands, but also enhanced CAR-T cell trafficking into the tumor.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…First, screening degranulation and cytokine-production against a panel of 10 PBT-TS lines, we observed that CLTX-EQ-28ζ CAR T cells displayed higher degranulation, but lower IFNγ production as compared to CLTX-CD8h-28ζ CAR T cells (Fig.S3, D and E). Next, the capacities of CLTX-EQ-28ζ and CLTX-CD8h28ζ CAR T cells to maintain long-term antitumor activity were evaluated in a repetitive tumor challenge assay (48). We observed that CLTX-EQ-28ζ, but not CLTX-CD8h-28ζ, CAR T cells retained activity through multiple rounds of tumor challenge ( Fig.…”
Section: Cltx-car T Cell Potency Can Be Optimized Through Modifying Nmentioning
confidence: 94%